A Case of Oral Histoplasmosis Concomitant with Pulmonary Tuberculosis - Silas Antonio Juvencio de Freitas Filho; Natália Galvão Garcia; Mário César de Souza; Denise Tostes Oliveira (Case Reports in Dentistry)
The superficial intraoral lesions of histoplasmosis occurring concomitant to tuberculosis, in a 46-year-old man, are reported. The human immunodeficiency virus (HIV) infection test was negative. The immunosuppression caused by tuberculosis in our patient probably had an important role in the development of intraoral lesions of histoplasmosis. Here, we discussed the role of the dentist in the diagnosis of these infectious diseases, highlighting the importance of anamnesis and the histopathology/immunohistochemistry exams.